Arguments from Developmental Order - Stöckle-Schobel, Richard (Frontiers in Psychology, 2016)
In this article, I investigate a special type of argument regarding the role of development in theorising about psychological processes and cognitive capacities. Among the issues that developmental psychologists study, discovering the ontogenetic trajectory of mechanisms or capacities underpinning our cognitive functions ranks highly. The order in which functions are developed or capacities are acquired is a matter of debate between competing psychological theories, and also philosophical conceptions of the mind – getting the role and the significance of the different steps in this order right could be seen as an important virtue of such theories. Thus, a special kind of strategy in arguments between competing philosophical or psychological theories is using developmental order in arguing for or against a given psychological claim. In this article, I will introduce an analysis of arguments from developmental order, which come in two general types: arguments emphasising the importance of the early cognitive processes and arguments emphasising the late cognitive processes. I will discuss their role in one of the central tools for evaluating scientific theories, namely in making inferences to the best explanation. I will argue that appeal to developmental order is, by itself, an insufficient criterion for theory choice and has to be part of an argument based on other core explanatory or empirical virtues. I will end by proposing a more concerted study of philosophical issues concerning (cognitive) development, and I will present some topics that also pertain to a full-fledged ‘philosophy of development’.